Bridging the Trust Gap: A Qualitative Analysis of Regulatory Stagnation and APEX-Driven Deposit Insurance for Baitul Maal wat-Tamwil in Indonesia - Adnan, Muhammad Akhyar; Nugroho, Randhy; Nurhayati, Ely (Universitas Muhammadiyah Yogyakarta, 2026)
Despite the rapid expansion of the formal Islamic financial sector in Indonesia, grassroots Islamic microfinance institutions—specifically Baitul Maal wat-Tamwil (BMT)—experience precarious growth largely attributed to a deficit in public trust. A critical factor driving this trust gap is the exclusion of BMTs from the national deposit insurance framework provided by the Indonesia Deposit Insurance Corporation (LPS). This study employs an exploratory qualitative case study design to investigate the legal, institutional, and operational frictions preventing the integration of BMTs into state-backed guarantee schemes. By triangulating data from elite informant interviews (policymakers from LPS, the Ministry of SMEs, and KNEKS) with a qualitative scoping questionnaire administered to 13 BMT managers, this research uncovers a landscape defined by regulatory arbitrage and institutional voids. To overcome this regulatory stagnation, this paper argues for the restart and operationalization of the APEX (Secondary Cooperative) model. Analyzed through the lens of the